A phase II randomized placebo‐controlled trial of pomegranate fruit extract in men with localized prostate cancer undergoing active surveillance. Issue 1 (23rd October 2020) - Jarrard, David; Filon, Mikolaj; Huang, Wei; Havighurst, Tom; DeShong, Katina; Kim, KyungMann; Konety, Badrinath R.; Saltzstein, Daniel; Mukhtar, Hasan; Wollmer, Barbara; Suen, Chen; House, Margaret G.; et al.
Abstract: Introduction or Objective: Men with favorable‐risk prostate cancer (PCa) on active surveillance may benefit from intervention strategies to slow or prevent disease progression and the need for definitive treatment. Pomegranate and its extracts have shown antiproliferative and proapoptotic effects in cell lines and animal models, but its effect on human prostate cancer as a target tissue remain unclear. Objectives of this trial include pomegranate's ability to alter serum and prostate tissue biomarkers and the ability of an active surveillance cohort to adhere to a chemoprevention trial for 1 year. Methods: Men with organ‐confined, favorable‐risk PCa on AS were randomly assigned to receive pomegranate fruit extract (PFE) 1000 mg ( n = 15) or placebo ( n = 15) once daily for twelve months. Prostate biopsies were performed at study entry and upon completion of the 1‐year intervention. Plasma and urinary biomarkers were analyzed utilizing immunoassays and HPLC. Tissue proteins were assessed by immunohistochemistry (IHC) and measured by automated quantitation. Results: PFE was well‐tolerated with no significant toxicities. One patient withdrew before study initiation and 29 completed the 1‐year intervention. No differences in plasma insulin‐like growth factor‐1 (IGF‐1) levels, prostate‐specific antigen doubling time, or biopsy kinetics were observed. Metabolites including urolithin A and urolithin A‐gluc were detected more frequently in the PFE arm in both urine and plasma ( p < .001 and p = .006, respectively). IHC analyses revealed reductions from baseline in 8‐OHdG (a DNA damage marker) ( p = .01) and androgen receptor expression ( p = .04) in prostate tumor associated with PFE treatment. Conclusion: PFE administration for 12‐month was well‐tolerated and the protocol followed in an active surveillance population. Analyses suggest that PFE contains bioactive compounds capable of altering biomarkers involving oxidative stress and androgen signaling in prostate tumor and normal‐appearing adjacent tissue. No alterations in the IGF axis were noted. This finding of study adherence and target activity provides a rationale for the further investigation of PFE in the active surveillance population.